QUALITY OF SERVICE USE COMMUNITY HEALTH INSURANCE (JAMKESMAS at BP RSUD Pringsewu LAMPUNG) - Bachtra Triansyah; Fitriyah .; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
This research entitled